Tasāhul Al-Tirmidhī terhadap Status Hukum Hadis: Analisis Pandangan Ulama - Muhammad Yusuf (Universitas Islam Negeri Mataram, 2014)
Calling al-Tirmidhī as mutasāhil is controversial both amongst classical and contemporary Muslim scholars. Some other scholars call him mutashaddid. Such an accusation to him is due to some factors. First, the difference of his Makhtūtat and his al-Jāmi‘ about particular status of ḥadīth. Second, scholars misunderstand about technical terms used by al-Tirmidhī in his work of al-Jāmi‘. Third, al-Tirmidhī elevates the status of ḥadīth ḍa‘īf into ḥasan because of support from other riwāyah of it. Moreover, he also justifīes ḥadīth ḥasan, if supported by other riwāyah, as ḥasan ṣaḥīḥ although this ḥadīth does not reach the status of valid. Forth, the title as tasāhul or tashaddud falls in the field of ijtihād, which may vary from one scholar to another. This means that the title of tasāhul or tashaddud ascribed to al-Tirmidhī may be accepted by some scholars while rejected by others.